ANALISIS PENGARUH MANAJEMEN ASET, SISTEM PENGENDALIAN INTERNAL PEMERINTAH DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENDAPATAN DENGAN OPTIMALISASI ASET IDLE SEBAGAI VARIABEL INTERVENING - Kurniyanta, Aan; Roziq, Ahmad; Sularso, Raden Andi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Abstract: This study aims to analyze the effect of asset management, government internal control system, and human resource competency on the revenue with idle asset optimization as the intervening variable, in the Office of State Assets and Auction Service, Jember. This study also aims to determine the best strategy for the state assets management, especially the idle asset, to increase national revenue. This is an explanatory research with applying mixed method approach using embedded concurrent model. The primary data were analyzed using Partial Least Square and descriptive analysis. The sample consists of 43 respondents collected using purposive sampling method. The results show that asset management, government internal control system, and human resource competency have no significant effects on idle asset optimization. Asset management and idle asset optimization have no significant effects on revenue, while government internal control system has a negative and significant effect on the revenue. Human resource competency has a positive and significant effect on the revenue. The results of qualitative descriptive analysis conclude that many working units did not optimally manage the asset utilization. Therefore, the right policy strategy is needed to improve idle asset optimization. Keywords: Asset Management, Government Internal Control System, Human Resource Competency, Idle Assets Optimization, and Revenue.